Cultural-Historical Foundations of School Course in Biology - Suchorukova L.N; Isaev E.I (Moscow State University of Psychology and Education, 2020)
The article analyzes the provisions of the cultural-historical psychology that serve as a theoretical and methodological basis for the practice of general education in biology. International monitoring of educational achievements reveals low biological literacy of Russian schoolchildren. The authors see the main reason in the insufficiently thought-out selection of the subject content. In middle school courses, it is mostly empirical, reduced to the study of the structure and functions of organisms and their diversity. In high school courses, it is theoretical, but theoretical concepts are given in a ready-made form, are not sufficiently interconnected and are often reduced to dictionary definitions, which negatively affects the development of cognitive and personal abilities of students. Currently, general biological education is being reformed, and the concentric construction of the subject content is being replaced with a linear one, which completely eliminates theoretical concepts from the middle school courses. The authors see the solution to the problem in updating the content of the school course in biology. As a methodological basis for the selection of content, a system approach is considered, the provisions of which were implemented by L.S. Vygotsky in the construction of the subject area of the cultural-historical psychology. Vygotsky's ideas about developmental learning and their further elaboration in the general psychological and psychological-pedagogical theory of activity are suggested as a theoretical basis for the organization of the educational process. Special attention is paid to the theory of learning activity developed in the works of D.B. Elkonin, V.V. Davydov, their disciples and followers. The paper presents the concept of the content for the school course in biology and describes the experience of its implementation.